2022
DOI: 10.3390/ijms23020705
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-Metastatic Role of the Novel miR-CT3 in Tumor Angiogenesis and Osteosarcoma Invasion

Abstract: Osteosarcoma (OS) is the most common primary bone tumor mainly occurring in young adults and derived from primitive bone-forming mesenchyme. OS develops in an intricate tumor microenvironment (TME) where cellular function regulated by microRNAs (miRNAs) may affect communication between OS cells and the surrounding TME. Therefore, miRNAs are considered potential therapeutic targets in cancer and one of the goals of research is to accurately define a specific signature of a miRNAs, which could reflect the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Osteosarcoma (OS) is the most common primary malignant tumor of bone in children and adolescents, it poses a significant clinical challenge with limited treatment options and poor prognosis. [1][2][3][4] Novel therapies to slow the progression and eradicate the disease [5][6][7][8][9] and the development of novel predictive culture systems resembling the native three-dimensional (3D) tumor microenvironment are required. 10 The development of advanced scaffold systems that mimic the native extracellular matrix (ECM) and provide a suitable microenvironment for tumor modeling and therapeutic evaluation is crucial for enhancing our understanding and improving treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteosarcoma (OS) is the most common primary malignant tumor of bone in children and adolescents, it poses a significant clinical challenge with limited treatment options and poor prognosis. [1][2][3][4] Novel therapies to slow the progression and eradicate the disease [5][6][7][8][9] and the development of novel predictive culture systems resembling the native three-dimensional (3D) tumor microenvironment are required. 10 The development of advanced scaffold systems that mimic the native extracellular matrix (ECM) and provide a suitable microenvironment for tumor modeling and therapeutic evaluation is crucial for enhancing our understanding and improving treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common primary malignant tumor of bone in children and adolescents, it poses a significant clinical challenge with limited treatment options and poor prognosis 1–4 . Novel therapies to slow the progression and eradicate the disease 5–9 and the development of novel predictive culture systems resembling the native three‐dimensional (3D) tumor microenvironment are required 10…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they confirmed that VEGF-A is a directed target of miR-CT3 and showed that its enforced expression in SAOS-2 and MG-63 cells reduced not only the expression of VEGF-A mRNA and protein, but also inhibited OS cell migration and invasion. In addition, they reported that miR-CT3 activated the p38 MAP kinase pathway and reduced the expression of EMT players such as vimentin [ 7 ].…”
mentioning
confidence: 99%